ПРИМЕНЕНИЕ ТЕХНОЛОГИИ РАЗВИТИЯ КРИТИЧЕСКОГО МЫШЛЕНИЯ ЧЕРЕЗ ЧТЕНИЕ И ПИСЬМО ПРИ ИЗУЧЕНИИ ПОЭМЫ А.С.ПУШКИНА «МЕДНЫЙ ВСАДНИК» В ВУЗЕ - Ешниязова, Э.Н. (SCIENCE and SOCIETY, 2019)
There are analysed the technology of developing critical thinking through reading and writing, methods and ways which are used in learning a poem “Copper Rider” by AS.Pushkin.